PERLINDUNGAN HUKUM PEMEGANG JAMINAN KEBENDAAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 67/PUU-XI/2013 - Bintang Aulia Hutama; Tri Sadini Prasatinah Usanti (Jurnal HUKUM BISNIS, 2018)
There is an adagium that the material guarantees holder have an absolute right to be enforced when juxtaposed with individual guarantees holder. Decision of the Constitutional Court number 67 / PUU-XII / 2013 laid down the payment of wages of workers should take precedence of payment when juxtaposed with the payment of creditors separatis and state claim rights. Based on the decision of the Constitutional Court above, it can be concluded that material rights are not always absolute. It is a big question about the existence of a material right that can be upheld when compared to individual guarantor holders.Keyword : Material Guarantees Holder, Constitutional Court Decision, labor wages